MEDIUM CHAIN FATTY ACIDS (MCFA) PROFILE AND CHEMICAL PROPERTIES OF COCONUT OILS (VIRGIN COCONUT OIL/VCO, SIMPLAH OIL, PLIEK U OIL, KLENTIK OIL, AND COPRA OIL) COMPARE TO PALM OIL - Normalina Arpi (Jurnal Sagu, 2013)
Medium Chain Triglyceride or Medium Chain Triacylglycerol (MCT) is triglyceride (triacylglycerol) thatcontains medium chain fatty acids C6:0 - C12:0, therefore is also known as Medium Chain Fatty Acid(MCFA). The type and amount MCFA of an oil are affected by the source, technique, and conditions toextract the oil. MCFA increasingly play important roles in terms of food processing technology,pharmacology, and clinical nutrition. The purpose of this study was to determine and compare the profile ofMCFA and chemical properties of coconut oil (VCO, simplah oil, pliek u oil, klentik oil, oil from copra) andpalm oil. The observed parameters were the type and amount of fatty acids, moisture content, free fatty acid,peroxide and iodine number. The results showed that the MCFA profiles of various coconut oil is almostsimilar, although the manufacturing process is different, however the profiles different from that of palm oilwhich the MCFA were not undetected. Coconut oil (VCO, simplah oil, pliek u oil, and klentik oil) containfatty acids of C6:0-C18:1, and klentik oil also contains C18: 2. From all types of the coconut oils used, thetotal content of MCFA (C6 + C8) ranged from 9.89-10.99%, fatty acids C6 + C8 + C10 were 17.94-20.21%,and total content of MCFA (C6 + C8 + C10 + C12) ranged between 54.91 in pliek u oil and the highest61.68% in the VCO. All types of coconut oil used in this study have met the SNI (01-2904-1992) and for palmoil, SNI (01-2901-1992). The best quality of oils obtained from the VCO V1 with levels of water 0.20%, freefatty acid (FFA) 0.22%, iodine number of 8.17%, and peroxide number of 0.96 mg O2 / g sample.Key words: MCT or MCFA, coconut oil, VCO, simplah oil, pliek u oil, klentik oil, copra oil, palm oil